2012
DOI: 10.1039/c2mt20013a
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and metabolism of selenite and selenomethionine in the Japanese quail

Abstract: Compared to the many studies on the physiological and toxicological effects of selenium (Se) in mammals, avian Se metabolism is still an unexplored topic. Some birds are useful as poultry for human nutrition. Moreover, birds belong to higher trophic levels in the biosphere and thus may play an important role in Se circulation in the ecosystem in the same way as mammals do. In this study, we analyzed the distribution and metabolism of Se in an experimental bird, the Japanese quail, which was fed drinking water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
(38 reference statements)
2
12
0
Order By: Relevance
“…The highest Se concentrations were in the kidneys, followed by liver, pancreas, lungs, brain and muscle, which had the lowest Se concentrations in mg/kg. This distribution pattern of Se found in different organs and tissues was in accordance with patterns reported by others (Nakayama et al., ; Anan et al., ). Anan et al.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The highest Se concentrations were in the kidneys, followed by liver, pancreas, lungs, brain and muscle, which had the lowest Se concentrations in mg/kg. This distribution pattern of Se found in different organs and tissues was in accordance with patterns reported by others (Nakayama et al., ; Anan et al., ). Anan et al.…”
Section: Discussionsupporting
confidence: 92%
“…The highest Se concentrations were in the kidneys, followed by liver, pancreas, lungs, brain and muscle, which had the lowest Se concentrations in mg/kg. This distribution pattern of Se found in different organs and tissues was in accordance with patterns reported by others (Nakayama et al, 2007;Anan et al, 2012). Anan et al (2012) followed the uptake of selenite and SeMet in Japanese quail and reported that the Se uptake to internal organs of SeMet was much higher than from selenite.…”
Section: Total Se and S Concentrations In Different Organs And Tissuessupporting
confidence: 91%
See 1 more Smart Citation
“…There is little information concerning relationship between Se in muscle or other tissues and feather of poultry. Quails fed drinking water with added SS or SeMet had the highest Se concentrations in the pancreas, followed by the down feathers, liver, and kidney [30]. Sevcikova et al [4] observed that Se concentrations in breast muscle and feather of 35-d-old broilers increased accordingly with dietary Se supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, four selenosugars were identified in liver, serum and urine of quail [34], turtle [35], rat [36], porcine [37], and human [38], including methyl-2-acetamido-2-deoxy-1-seleno-β-D-galactopyranoside (selenosugar 1) [39,40], methyl-2-acetamido-2-deoxy-1-seleno-β-D-glucosopyranoside (selenosugar 2) [40], and methyl-2-amino-2-deoxy-1-seleno-β-D-galactopyranoside (selenosugar 3) [40] and selenosugar A [41]. In urine samples, selenosugar 1 is the major metabolite.…”
Section: Speciation Of Sementioning
confidence: 99%